THE INFLUENCE OF REGIONAL BACKGROUND AND INCLUSIVITY OF PRIDE EVENTS TO THE MENTAL WELLBEING OF LGBTQ+ PEOPLE - Rakesh, Sarpal; Lim, Emily, Fong Yee (INTI International University, 2023)
This literature review attempted to answer the reason of the LGBTQ+ community in gaining more support presently by utilising the approach of structuralism and poststructuralism theoretical methods. Then, the mental health of the sexual minorities is critically assessed through the kaleidoscopic lenses of regional backgrounds, specifically the influence of cultural and religion upbringing towards the degrees of acceptance in LGBTQ+ people. The inclusivity of pride events to the mental wellbeing of the LGBTQ+ people had been deliberately reflected and justified through research findings and statistical data. Ultimately, the implications had been given to event organisers and corporates to have better scope in understanding the niche market of LGBTQ+ consumers. This literature review can be momentous for future researcher to endeavour a finer and comprehensive investigation on the subject matters in this study.